Praktik Baik Manajemen Menuju Usaha Mikro, Kecil dan Menengah (UMKM) Mandiri dan Produktif di Kampung Bulak Timur, Kelurahan Cipayung, Kota Depok, Jawa Barat - Bernadin Dwi Mardiatmi; Anita Nopiyanti; Anggi Angga Resti (Yumary: Jurnal Pengabdian kepada Masyarakat, 2022)
Purpose: to provide education to MSME business actors on good management practices in managing and determine MSME management models that can realize good management practices as an effort to improve MSME management performance. This management model contains aspects of company management, namely marketing management, production management, financial management, and human resource management. Method: The method used is to provide education and literacy about good managerial practices. The material provided includes general management and human resources, production management, financial management, and marketing management. In measuring the level of understanding of participants before giving the material and filling out the post-test after the material is given. In addition, questionnaires were filled out to develop participants' understanding of good management practices using analytical indexes. Results: The result of this study is an increase in understanding of management practices as seen from the increase in the average pre-test of 5.56, increasing in the post-test to 7.31. MSMEs actors understand the material provided on general management and human resources, production management, financial management, and marketing management. Based on the index analysis, the participants' level of understanding of the material on human resource management, marketing management, production management, and financial management is in the high category. Conclusions: Educational and literacy activities about good management practices can increase partners' knowledge about aspects of business management and can put this knowledge into practice in business progress.